KOMUNIKASI INTERPERSONAL ORANG TUA BEKERJA DENGAN ANAK BERPRESTASI DI SMA NEGERI 1 LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Rio Alfian; Ernita Arif; Sarmiati Sarmiati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Interpersonal communication between parents and children has a significant impact on the mental growth and academic performance of children. As a result, parents must make the effort to engage with their kids. Based on previous study, children who have working parents typically perform worse academically. Nevertheless, some children of working parents still achieve success. This research was conducted to determine the communication style of working parents with academically gifted children. A case study methodology and a qualitative technique are both used in this research. Observation, interviews and documentations are used as data collection methods. The results of this research suggest that parental and child interpersonal communication activities have a significant impact on children's mental development. Children's self-confidence will be cultivated through effective parent-child contact and communication, especially when it comes to the children's belief in their own potential to succeed.